The Influence of Teachers as Role Models in Madrasah Ibtidaiyah: Impact on Students' Moral and Ethical Development - Arni Arni; Musyarrafah Sulaiman Kurdi; Muqarramah Sulaiman Kurdi (Politeknik Kampar, 2023)
This research explores the influence of teachers as role models in Madrasah Ibtidaiyah or Madrasah Ibtidaiyah and its impact on students' moral and ethical development. The study adopts a library research approach, utilizing existing literature, scholarly articles, and relevant texts to gather information and insights. The research employs a descriptive analysis method to analyze the collected data and examine the specific practices and qualities that make teachers effective role models in this context. The study also explores the long-term effects of teachers' positive moral and ethical influence on students, exploring how these effects manifest in their personal lives, relationships, and contributions to society. The research also explores how teachers can address students' contemporary moral and ethical challenges, such as social media influences, cultural diversity, and globalization, while remaining true to Islamic values and teachings. Moreover, the study describes the internalization of their teachers' moral and ethical behaviours and the subsequent impact on their moral decision-making processes and behaviour outside of the educational context. This research aims to contribute to understanding the crucial role that teachers play as role models in madrasah ibtidaiyah and its implications for students' moral and ethical development.